Exploring Conflict Management Using Qualitative Approach - Yazid, Zaleha (Master of Management, Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
This paper focuses on qualitative methods in researching the area of conflict management, specifically in Self-Managed Project Team (SMPT). The research aims to explore the evolvement of conflict management strategies in SMPT as this type of team is given the responsibility to solve problems and make decision by themselves. The inductive approach will overcome the limitation of quantitative method in management research as one of its objectives is to explain the different elements of the explored social system and their interconnection. Hence, it aims at the contextual understanding of social behavior rather than extensive measurement. This paper also includes the research activities in details such as the data collection methods which involved semi-structured interviews and weekly telephone interviews. The findings of the research proposed that conflict management strategies in SMPT changes over time from confrontation and cooperative style towards avoidance due to the issues of reputation and the deadline.